"Take hold of the robe of a Jew": Herbert of Bosham's Christian hebraism - Goodwin, Deborah L. (Studies in the history of Christian traditions, 2006)
The life of a twelfth-century intellectual -- Herbert of Bosham's Psalterium cum commento -- Twelfth-century Christian hebraism in context -- Colonizing the territory of Scripture -- The linguistic and cultural horizons of Herbert's hebraism -- Herbert's hermeneutic of the literal sense -- Herbert as expositor : the faithful synagogue